Mindful practice for teachers: Relieving stress and enhancing positive mindsets - Carroll, Annemaree; Hepburn, Stevie-Jae; Bower, Julie (Frontiers in Education, 2022)
Objectives: The present study aimed to determine the degree of stress relief and increase in mindfulness attributes experienced by 18 participants in an eight-week Mindful Practice for Teachers (MPT) program. Methods: The mixed-methods study design included participant reflections collected throughout the study and self-report measures: Perceived Stress Scale (PSS), Positive Mindset Index (PMI) and Five Facets of Mindfulness Questionnaire (FFMQ). Data analysis: Pre- and post-program paired-samples t-tests were completed for the self-report measures. Inductive coding was completed for the participant reflections. Results: The participants (N = 18) reported a significant decrease in perceived stress pre-program and post-program. The significant changes in the sub-scales of the FFMQ were reported for observing , non-reaction and nonjudgement pre-program and post-program. A statistically significant change was reported for the PMI sub-scale stability (p = .029) which increased post-program. According to participant reflections, there was an increased awareness of the physiological response during positive and challenging events/incidents. The participants reported positive satisfaction pertaining to program materials, exercises, and activities. Conclusions: Findings indicated that the participants experienced a decrease in their perceived level of stress and an increase in their mindfulness attributes consequently highlighting the benefits of mindfulness-based programs for teacher stress management. The MPT program may prove to be a positive intervention for managing work-related stress and providing teachers with simple, stress management resources.